2001
DOI: 10.2118/72502-pa
|View full text |Cite
|
Sign up to set email alerts
|

Relative Permeability Measurements for Post-Waterflood Depressurization of the Miller Field, North Sea

Abstract: This paper describes a determination of critical gas saturations and relative permeabilities relevant to the depressurization of the Miller field. A series of reservoir-condition coreflood experiments and associated numerical simulations is described. Three experiments were conducted with aged Miller core and fluids at 120°C. Each was comprised of a waterflood at about 414 barg, followed by depressurization at different rates. The laboratory data included extensive three-phase in-situ saturation measurements t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…However, in a recent study, Bagudu et al (2018) showed that critical gas saturation is a weak function of the depressurizing rate for a low permeable porous medium. In their study, they decreased the depressurizing rate three orders of magnitude (100psi/day to 1psi/day), but no significant change in the critical gas saturation was observed, agreeing with the experimental results from some earlier studies (Drummond et al, 2001;Egermann and Vizika, 2000;Naylor et al, 2001) Since Handy (1958) and Stewart et al (1952) highlighted the similarity between relative permeabilities and oil recovery under reservoir conditions between external gas drive and solution gas drive, many works have discussed similarities and distinctions between the two flow regimes (Drummond et al, 2001;Egermann and Vizika, 2000;Firoozabadl et al, 1992;Naylor et al, 2001). This calls for direct measurements of the oil relative permeabilities under the solution gas drive in the region where the liberated gas is immobile.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, in a recent study, Bagudu et al (2018) showed that critical gas saturation is a weak function of the depressurizing rate for a low permeable porous medium. In their study, they decreased the depressurizing rate three orders of magnitude (100psi/day to 1psi/day), but no significant change in the critical gas saturation was observed, agreeing with the experimental results from some earlier studies (Drummond et al, 2001;Egermann and Vizika, 2000;Naylor et al, 2001) Since Handy (1958) and Stewart et al (1952) highlighted the similarity between relative permeabilities and oil recovery under reservoir conditions between external gas drive and solution gas drive, many works have discussed similarities and distinctions between the two flow regimes (Drummond et al, 2001;Egermann and Vizika, 2000;Firoozabadl et al, 1992;Naylor et al, 2001). This calls for direct measurements of the oil relative permeabilities under the solution gas drive in the region where the liberated gas is immobile.…”
Section: Introductionsupporting
confidence: 89%
“…Often, the best option to extend a flooded reservoir's life in terms of cost, ease of implementation, and environmental impact, is depressurization below the bubble point. Thus, a great interest revived in the last two decades in both the oil industry and academia in considering depressurization as an improved oil recovery mechanism (de Mirabal et al, 1996;Goodfield and Goodyear, 2003;Jr et al, 2004;Lago et al, 2000;Ligthelm et al, 1997;Naylor et al, 2001;Thomas and Bratvold, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Network model simulations and experimental studies conducted to study gas nucleation during oil production (internal gas drive) agree with results presented above and show lower gas permeability than when gas is forced to invade the medium (external gas drive) [ Stewart et al ., ; Naylor et al ., ; Poulsen et al ., ; Yortsos and Parlar , ; Nyre et al ., ]. Published results also show that pore connectivity, depressurization rate, and pore size distribution affect the critical gas saturation when a gas cluster percolates, the generated gas bubble density, and relative gas permeabilities [ Poulsen et al ., ; Nyre et al ., ; Jang and Santamarina , ].…”
Section: Analyses and Discussionmentioning
confidence: 99%
“…Their approach, first presented by Mejia et al [] and further developed by Nordtvedt et al [], could incorporate the effects of fluid compressibility, capillary pressure, gravity, and heterogeneity. Naylor et al [], Drummond et al [], Egermann et al [], and Petersen et al [] also employed the history‐matching technique to deduce relative permeabilities during depressurization experiments. More examples of use of this method can be found in Table .…”
Section: Measurement Techniquesmentioning
confidence: 99%